Inappetens hos katt – omvårdnadsbehandlingar med fokus på beröring - Hallenbo Wahlqvist, Jennie (2014)
Particular to the cat among our pets is its´ unique nutritional needs and metabolism. The cat cannot produce some nutrients by themselves and must get them through their diet. This means that the cat quickly can suffer from various diseases unless the nutritional needs are covered. In those cases where man is completely in control of the cat’s diet, the right knowledge is crucial for the cat’s wellbeing. Inappetence means that the cat has lost his appetite and does not eat voluntarily. This is a common reason why cats are admitted for care at animal hospitals. The aim with this report is to gain a better understanding of inappetence in cats, its consequences and the nursing treatments that are available. Focus will be on human touch and the factors that influence why it could work as a nursing treatment. A literature study and interviews with veterinary nurses is the method of which the conclusions of this paper has been based upon.